2020
DOI: 10.1016/j.jalz.2019.08.191
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and neurocognitive decline in the Hispanic Community Health Study/Study of Latinos

Abstract: Introduction: To determine if sleep-disordered breathing (SDB), daytime sleepiness, insomnia, and sleep duration predict seven-year neurocognitive decline in US Hispanics/Latinos (N = 5247). Methods: The exposures were baseline SDB, daytime sleepiness, insomnia, and sleep duration. The outcomes were change in episodic learning and memory (B-SEVLT-Sum and SEVLT-Recall), language (word fluency [WF]), processing speed (Digit Symbol Substitution), and a cognitive impairment screener (Six-item Screener [SIS]). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…However, whether change of sleep duration itself or short sleep duration is the primary cause of higher MCI risk cannot be answered by our study. www.nature.com/scientificreports www.nature.com/scientificreports/ Regarding long sleep duration, several studies showed long sleep to be associated with impaired cognitive performance 13,[40][41][42] . For instance, Ramos et al (2019) 40 found long sleep (> 9 hours) to be predictive for seven-year cognitive decline in episodic learning and memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether change of sleep duration itself or short sleep duration is the primary cause of higher MCI risk cannot be answered by our study. www.nature.com/scientificreports www.nature.com/scientificreports/ Regarding long sleep duration, several studies showed long sleep to be associated with impaired cognitive performance 13,[40][41][42] . For instance, Ramos et al (2019) 40 found long sleep (> 9 hours) to be predictive for seven-year cognitive decline in episodic learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Regarding long sleep duration, several studies showed long sleep to be associated with impaired cognitive performance 13,[40][41][42] . For instance, Ramos et al (2019) 40 found long sleep (> 9 hours) to be predictive for seven-year cognitive decline in episodic learning and memory. Potvin et al (2012) 38 reported an increased OR for women sleeping ≥ 9 h (OR = 2.10 [1.10 to 4.00], reference> 5 to <9 h).…”
Section: Discussionmentioning
confidence: 99%
“…6,42,43 . A recent study assessed 5247 participants with in-home polysomnography and found no association between cognitive function and SDB assessments, including Epworth Sleepiness Scale and Respiratory Event Index 7 . Third, 15.9% of participants in Wave 1 lost to follow up in Wave 2 and 19.4% lost to follow up in Wave 3.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Experimental studies have showed associations between sleep, circadian rhythm, and neurodegenerative diseases, especially for Alzheimer's disease 4,5 . Under the guidance of this association, researchers pointed out that improvement in sleep duration might be a therapeutic target in dementia treatment or prevention [5][6][7] . Few studies have examined the effect of change in sleep duration on cognition.…”
Section: Considerable Studies Have Found Associations Between Sleep Amentioning
confidence: 99%
“…This theory that two or more insults that occur early in development may have synergistic repercussions later in life can be applied to the DOHaD hypothesis. For instance, hypertension [3,[9][10][11], stroke [12,13], neurodegenerative disorders [14,15], osteoporosis [16,17], sleep disorders [18][19][20][21][22][23][24][25], organ fibrosis [26][27][28], metabolic dysfunction [29][30][31][32][33] and cancer [34,35] are all diseases that have an onset in later life, and could be triggered by temporally proximate experiences, but the increased risk for these diseases could have a developmental origin. Furthermore, several disorders better appreciated for their developmental origins, such as Fetal Alcohol Spectrum Disorders (FASDs), are associated with premature aging [5], suggesting that early developmental experiences can influence the onset of diseases that are typically considered aging-related.…”
Section: Developmental Origins Of Health and Diseasementioning
confidence: 99%